Hemostatic effect of novel carbon dots derived from Cirsium setosum Carbonisata - Luo, Juan; Zhang, Meiling; Cheng, Jinjun; Wu, Shuhong; Xiong, Wei; Kong, Hui; Zhao, Yan; Qu, Huihua (RSC advances, 2018)
In this study, for the first time, we discovered novel water-soluble carbon dots (CDs, named CSC-CDs) from aqueous extracts of Cirsium setosum Carbonisata (CSC), which were uniform in size and possessed a nearly spherical shape, and the CDs exhibited low toxicity against RAW 264.7 cells by CCK-8 assay. Most importantly, tail hemorrhaging and liver hemorrhaging experiments showed that CSC-CD-treated mice had significantly shorter bleeding times than normal saline-treated mice. Coagulation assays suggested that the CSC-CDs could stimulate the extrinsic blood coagulation system and activate the fibrinogen system. These results suggested that the CSC-CDs have a remarkable hemostatic effect. The study provides evidence to support the further investigation of the considerable potential of carbon dots. We discovered novel water-soluble carbon dots from aqueous extracts of Cirsium setosum Carbonisata, which have a remarkable hemostatic effect. The study provides evidence to support the further investigation of considerable potential of carbon dots.